Rarely Reported Cryptobenthic Fish in Marine Caves of the Eastern Mediterranean Sea - Michail Ragkousis; Markos Digenis; Marcelo Kovačić; Stelios Katsanevakis; Vasilis Gerovasileiou (Journal of Marine Science and Engineering, 2021)
Data on the distribution and ecology of cryptobenthic fish of marine caves in the Mediterranean Sea are extremely scarce but necessary for scientists and marine managers alike in order to understand these fish’s ecological role and assess their conservation status. Broadscale surveys by implementing underwater visual census and photographic sampling in marine caves of the northeastern Mediterranean Sea, within different expeditions during the last 5 years, brought to light new records of eight rarely reported cryptobenthic fish species. To a smaller extent, complementary citizen science data from diving professionals of Crete were used to fill distribution gaps. A total of 36 new records (66 individuals) from 18 marine caves and caverns of the Aegean and northeastern Levantine Seas were assembled, belonging to the gobies Corcyrogobius liechtensteini, Didogobius splechtnai, Gammogobius steinitzi, and Thorogobius ephippiatus, the blenny Microlipophrys nigriceps, the tripterygiid Tripterygion melanurum, the speleophilic bythitid Grammonus ater, and the gobiesocid Lepadogaster cf. lepadogaster. The above species have been rarely reported from the Eastern Mediterranean Sea, with D. splechtnai and G. steinitzi being recorded for the first and second time from Greek waters, respectively, while L. cf. lepadogaster constitutes the second record of a clingfish species in a marine cave of the Aegean Sea. Interesting behavioral and ecological habits were also noted for some species, based on in situ observations and photographic evidence. Our study contributes to filling gaps in the knowledge of cave fish diversity and demonstrates that cryptobenthic mobile species in understudied cryptic habitats are more common than previously thought in the Mediterranean Sea.